Profile of Open Globe Injury in Children at Lumbini Eye Institute - Bhattarai, Binita; Pokhrel, Santosh; Thapa, Bel; Gautam, Prachand; Gurung, Nanda (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Ocular trauma is preventable public health problem throughout the world that especially affects the young. During the last several decades the prognosis of open-globe injuries has significantly improved. The aim of this study was to describe the clinical profile of open globe injury in children and visual outcome after surgery. MATERIAL AND METHODS: It is a prospective hospital based study that included children aged 1-15 yrs presenting to Lumbini Eye Institute (LEI), Bhairahawa with open globe injury. Visual acuity and Anterior and Posterior Segment examination findings were recorded at the time of presentation, after surgery and in three subsequent follow up visits. RESULTS: Out of 26,538 pediatric patients, during the study period 0.26% (n=69) had open globe injury. The most common age group was 510 years comprising 43.5%, with a strong male preponderance of 74% and mean age of 8.06±3.6years. Playing was the most common mode of injury comprising 58%, where as stick was the most common agent causing trauma consisting 51%. Fifty two percent were visually impaired and 39% were blind at the time of presentation and only 9% children had visual acuity better than 6/18. Improved vision was found in 52%, same vision in 34% and deteriorated vision in 13% till third follow up visit. Anatomical integrity of the globe was maintained in 88.4% and only 11.6% had Phthisis bulbi. CONCLUSION: The incidence of open globe injury among children at Lumbini Eye Institute was 0.26%. Male children were more vulnerable. Stick was the most common traumatizing agent. There was a favorable outcome with improved vision in most children after surgery. Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 37-40